SETX (senataxin), the helicase mutated in AOA2 and ALS4, functions in autophagy regulation. Issue 8 (3rd August 2021) - Richard, Patricia; Feng, Shuang; Tsai, Yueh-Lin; Li, Wencheng; Rinchetti, Paola; Muhith, Ubayed; Irizarry-Cole, Juan; Stolz, Katharine; Sanz, Lionel A.; Hartono, Stella; Hoque, Mainul; Tadesse, Saba; et al.
ABSTRACT: SETX (senataxin) is an RNA/DNA helicase that has been implicated in transcriptional regulation and the DNA damage response through resolution of R-loop structures. Mutations in SETX result in either of two distinct neurodegenerative disorders. SETX dominant mutations result in a juvenile form of amyotrophic lateral sclerosis (ALS) called ALS4, whereas recessive mutations are responsible for ataxia called ataxia with oculomotor apraxia type 2 (AOA2). How mutations in the same protein can lead to different phenotypes is still unclear. To elucidate AOA2 disease mechanisms, we first examined gene expression changes following SETX depletion. We observed the effects on both transcription and RNA processing, but surprisingly observed decreased R-loop accumulation in SETX-depleted cells. Importantly, we discovered a strong connection between SETX and the macroautophagy/autophagy pathway, reflecting a direct effect on transcription of autophagy genes. We show that SETX depletion inhibits the progression of autophagy, leading to an accumulation of ubiquitinated proteins, decreased ability to clear protein aggregates, as well as mitochondrial defects. Analysis of AOA2 patient fibroblasts also revealed a perturbation of the autophagy pathway. Our work has thus identified a novel function for SETX in the regulation of autophagy, whose modulation may have a therapeutic impact for AOA2. Abbreviations: 3ʹREADS: 3ʹ region extraction and deep sequencing; ACTB: actin beta; ALS4: amyotrophic lateral sclerosis type 4; AOA2: ataxia with oculomotor apraxia type 2; APA: alternative polyadenylation; AS: alternative splicing; ATG7: autophagy-related 7; ATP6V0D2: ATPase H+ transporting V0 subunit D2; BAF: bafilomycin A1 ; BECN1: beclin 1; ChIP: chromatin IP; Chloro: chloroquine; CPT: camptothecin; DDR: DNA damage response; DNMT1: DNA methyltransferase 1; DRIP: DNA/RNA IP; DSBs: double strand breaks; EBs: embryoid bodies; FTD: frontotemporal dementia; GABARAP: GABA type A receptor-associated protein; GO: gene ontology; HR: homologous recombination; HTT: huntingtin; IF: immunofluorescence; IP: immunoprecipitation; iPSCs: induced pluripotent stem cells; KD: knockdown; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MN: motor neuron; MTORC1: mechanistic target of rapamycin kinase complex 1; PASS: PolyA Site Supporting; PFA: paraformaldehyde; RNAPII: RNA polymerase II; SCA: spinocerebellar ataxia; SETX: senataxin; SMA: spinal muscular atrophy; SMN1: survival of motor neuron 1, telomeric; SQSTM1/p62: sequestosome 1; TFEB: transcription factor EB; TSS: transcription start site; TTS: transcription termination site; ULK1: unc-51 like autophagy activating kinase 1; WB: western blot; WIPI2: WD repeat domain, phosphoinositide interacting 2; XRN2: 5ʹ-3ʹ exoribonuclease 2.